Highly branched dextrin prepared from high-amylose maize starch using waxy rice branching enzyme (WRBE). (15th July 2016) - Tian, Yaoqi; Chen, Huangli; Zhang, Xiwen; Zhan, Jinling; Jin, Zhengyu; Wang, Jinpeng
Highlights: Branching enzyme (BE) was isolated from the developing waxy rice seeds. The hydrolysis and the transglycosylation abilities of the BE were evaluated. BE catalyzed HAMS to form a new dextrin with highly branched side chains. BE might inhibit starch retrogradation and control the blood glucose level. Abstract: Branching enzyme (BE, EC 2.4.1.18) was isolated from the developing waxy rice endosperm and used to prepare a highly branched dextrin based on high-amylose maize starch (HAMS) as a substrate. The molecular mass of the starch initially degraded quickly from 2.5 × 10 7 to 4.1 × 10 5 Da, and then stabilized, with a minimal increase during the BE treatment. The resultant branched dextrin had a narrow size distribution, with a mean molecular weight of 5.1 × 10 5 Da and a polydispersity index (PI) of 1.567. The results of high-performance anion exchange chromatography indicated that the degree of polymerization (DP) of the branched chains ranged from 3 to 27; approximately 75.26% of these chains were short (DP < 10). These findings suggest that the isolated BE can cleave long chains into oligosaccharides, subsequently transferring oligosaccharides into highly branched dextrins with a narrow size distribution and short side chains.